The Influence of Entrepreneurs on the Development of Islamic Educational Institutions - Ansisca, Ansisca (Penerbit Hellow Pustaka, 2025)
The objective to be achieved in this study is to determine the role of merchants in the development of Islamic educational institutions. This study uses a qualitative approach (descriptive qualitative), in the form of literature studies and content analysis approaches to collect relevant information related to the topics or problems discussed. Data collection techniques are carried out through in-depth studies of various sources, such as books, academic literature, and research reports related to the problems raised. According to the results of research conducted by researchers, it was found that the role of merchants or traders in the development of educational institutions has a significant contribution that goes beyond economic activities alone. This article explores how merchants support the growth of education through the provision of funds, dissemination of knowledge, development of educational infrastructure, and the sowing of social and religious values. Using a historical approach, the discussion includes concrete examples of the role of merchants during the Srivijaya era, the Aceh Sultanate, and trade networks in the archipelago. The results of the study show that merchants not only play a role as financial supporters of educational institutions, but also as globalization connectors that bring educational ideas and innovations from various parts of the world. Their contributions have a long-term impact on community development, both in social, economic and cultural aspects. This study emphasizes the importance of synergy between the economic and educational sectors in creating a sustainable civilization.